Study on factors affecting the droplet temperature in plasma MIG welding process - Mamat, Sarizam (2018)
In the present study, the mechanism to control droplet temperature in the plasma MIG welding was discussed based on the measurements of the droplet temperature for a wide range of MIG currents with different plasma electrode diameters. The measurements of the droplet temperatures were conducted using a two color temperature measurement method. The droplet temperatures in the plasma MIG welding were then compared with those in the conventional MIG welding. As a result, the droplet temperature in the plasma MIG welding was found to be reduced in comparison with the conventional MIG welding under the same MIG current. Especially, when the small plasma electrode diameter was used, the decrease in the droplet temperature reached maximally 500 K. Also for a particular WFS, the droplet temperatures in the plasma MIG welding were lower than those in the conventional MIG welding. It is suggested that the use of plasma contributes to reduce the local heat input into the base metal by the droplet. The presence of the plasma surrounding the wire is considered to increase the electron density in its vicinity, resulting in the arc attachment to expand upwards along the wire surface to disperse the MIG current. This dispersion of MIG current causes a decrease in current density on the droplet surface, lowering the droplet temperature. Furthermore, dispersed MIG current also weakens the electromagnetic pinch force acting on the neck of the wire above the droplet. This leads to a larger droplet diameter with increased surface area through lower frequency of droplet detachment to decrease the MIG current density on the droplet surface, as compared to the conventional MIG welding at the same MIG current. Thus, the lower droplet temperature is caused by the reduction of heat flux into the droplet. Consequently, the mechanism to control droplet temperature in the plasma MIG welding was clarified.